Social media and political accountability: An exploratory analysis of the impact of facebook and twitter in Punjab Pakistan - Saiqa, Sadiq (2021)
An extensive review of the burgeoning literature on the impact of social media in Governance and politics, revealed a serious absence of consensus over its workability in enhancing and promoting accountability in governance. The level of inconsistency in findings as well as the rapidly existing dynamism within the subject invariably makes it a novel research area especially within the context of Pakistan where researches of this nature are still at the infancy level. It is therefore imperative a to explore the potency of social media in promoting accountability within the Pakistani context. More so, as there is an absence of empirically-driven study using resource mobilization theory and public sphere theory that comfy the resource mobilization and provision of low-cost information for pursuit of political accountability and create virtual sphere, for everyday political discussion in the social media particularly on Facebook and Twitter. This study added value to current literature by explaining the impact of social media in promoting political accountability in Pakistani context. In doing so the study explored the responsiveness of the political institution to trust of the political accountability reposted on them, its further explored the current state of freedom of expression which served as a yardstick for better understanding of the impact of social media in promoting political accountability in Pakistan and directions of reforms that can enhance the impact of social media towards political accountability in Pakistan. The study finds out that social media is significantly contributing in pursuit of accountability, though political distrust and non-supporting legal mechanism constitute some of the structural encumbrances against the workability of social media in pursuing and ensuring political accountability in Pakistan. Therefore, political and legal reforms are indispensable to promote political accountability in the country. The study was conducted in Punjab that is most populated province among total of four provinces of Pakistan, more than half of total population resided in Punjab. The study espouses an ethnographic strategy in which data were collected by in depth semi structured interviews, qualitative content analysis of social media applications and personal observation. Twenty informants participated in semi structured interviews rolled out the politicians, journalists, academics, social media bloggers and legal practitioners. The data was thematically analyzed by keeping in view previous literature and theoretical framework in which political accountability, participation, information dissemination, freedom of expression were identified in democratic system and discussed.